A North Star for Gerontology: Using the Threshold Concept Framework to Transform Ageism Education. (27th September 2021) - Janssen, Leah M; Flores, Valerie; Cao, Jiawei
Abstract: Threshold concepts are fundamental to the learning process and are said to transform the way we view and understand the world around us. Although a new framework to gerontology, the threshold concept framework has been utilized in many fields inside (e.g., psychology, social work) and outside (e.g., clinical and research settings) of academia. This framework facilitates understanding learning, exposing expert blind spots, and designing curricula for complex concepts that are challenging to learn. For decades gerontologists have grappled with ageism and its dire consequences including unemployment, negative health outcomes, and rationing of health care. Education is one of, if not the most, powerful tools to combat ageism. This article demonstrates the utility of the threshold concept framework for gerontologists by conceptualizing ageism as a threshold concept. The purpose of this article is to provide an innovative approach to education on complex gerontological topics in different clinical, research, and educational settings using ageism as a primary example of a threshold concept in gerontology.